2006
DOI: 10.1157/13094026
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of preseasonal sublingual immunotherapy with grass pollen carbamylated allergoid in rhinitic patients. A double-blind, placebo-controlled study

Abstract: The results of this study show that the allergoid SLIT is safe and effective in decreasing symptom scores and drug use in rhinitic patients allergic to grass pollen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…The duration of SLIT courses varied from 3 months (minimum duration) to 3 years (maximum duration). The administration regimen was preseasonal in three studies (27,32,44), co-seasonal in three (15,42,47), and continuous in eight trials (30,35,38,39,41,43,46,54), despite the allergen was seasonal. In the remaining 27 trials the adopted regimen was precoseasonal.…”
Section: Literature Analysismentioning
confidence: 99%
“…The duration of SLIT courses varied from 3 months (minimum duration) to 3 years (maximum duration). The administration regimen was preseasonal in three studies (27,32,44), co-seasonal in three (15,42,47), and continuous in eight trials (30,35,38,39,41,43,46,54), despite the allergen was seasonal. In the remaining 27 trials the adopted regimen was precoseasonal.…”
Section: Literature Analysismentioning
confidence: 99%
“…1). They comprised a total of 3160 SIT-treated participants [SCIT with natural extracts: 440 subjects in seven trials (17)(18)(19)(20)(21)(22)(23); SCIT with allergoids: 168 SIT-treated subjects in three trials (24)(25)(26); SLIT with natural extract drops: 906 SIT-treated subjects in 16 trials (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42); SLIT with allergoid tablets: 41 SIT-treated subjects in two trials (43,44); SLIT with natural extract tablets: 1605 SIT-treated subjects in five trials (45)(46)(47)(48)(49)(50)]. The main reasons for excluding studies were lack of double-blinding/ randomization, review articles, multiple allergen extracts, outcomes unrelated to efficacy and preparations that are not commercially available.…”
Section: Resultsmentioning
confidence: 99%
“…Few or no local AEs were reported (12% in the active group in Palma-Carlos et al), and no systemic AEs were observed (43).…”
Section: Safetymentioning
confidence: 93%
See 1 more Smart Citation
“…However, the risk of inducing side effects, sometimes associated with the injection of the above products [28], has led allergen manufacturers to explore safer therapeutic modalities. KCNO-modified allergens have proven useful for developing original, safe and effective products such as monomeric allergoids [18,29,30,31,32,33,34,35,36]. An analogous approach has been performed on DP pollen extract.…”
Section: Discussionmentioning
confidence: 99%